A new cavability index in block caving mines using fuzzy rock engineering system. (July 2015) - Rafiee, R.; Ataei, M.; KhalooKakaie, R.
Abstract: A new cavability index (CI) for block caving mines is introduced. The interaction matrix based on the rock engineering system (RES), that analyzes the interrelationship between the parameters affecting rock engineering activities, is used to study rock mass cavability. Since the value of interaction in the RES method is not unique, the fuzzy system is used to minimize subjectivity of the weights which are computed in the RES method. As a result, an index is presented to predict the cavability potential of rock masses. The Palabora mine was selected as a case study and the proposed index was used to rank the three geological units in this mine. It was observed that the rock cavability index could suitably predict rock masses condition from caving point of view. The newly proposed approach could be a simple but efficient tool in evaluation of the parameters affecting the cavability of rock mass in block caving mines and hence be useful in decision making under uncertainties. Highlights: We introduce a new cavability index in block caving mines. The important parameters in cavability have been investigated. A fuzzy system is designed to improve the ESQ coding method.